Static Load Evaluation of Kaplan Turbine Shaft in Hydraulic Pump System Using Finite Element Analysis (FEA) Method: Evaluasi Beban Statis Poros Turbin Kaplan Pada Sistem Pompa Hidrolis Menggunakan Metode Finite Element Analysis (FEA) - Haykal Muzakki; Udin Komarudin; Adhita Prasetia (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2026)
The turbine shaft is a critical component in hydraulic pump systems as it transmits mechanical energy from the turbine to the pump and experiences combined loads during operation. This study aims to evaluate the structural safety of the turbine shaft geometry under operational loading conditions using the Finite Element Analysis (FEA) method. A three-dimensional shaft model was developed based on actual field measurements and analyzed using SolidWorks Simulation with a torsional load of 6.016 × 10³ Nm calculated from a turbine power of 157.5 kW and a rotational speed of 250 rpm. The shaft material used was SCM4 (AISI 4140). Simulation results show a maximum von Mises stress of 75 MPa with a safety factor of 8.27 relative to the material yield strength. The maximum displacement of 0.4 mm and maximum strain of 2.9 × 10⁻⁴ remain within the elastic range of the material. The results indicate that the shaft design is theoretically safe under static loading; however, indications of wear observed in the field suggest the influence of long-term mechanical degradation during operation.